Long‐Lived Charge Separation in Novel Axial Donor–Porphyrin–Acceptor Triads Based on Tetrathiafulvalene, Aluminum(III) Porphyrin and Naphthalenediimide. Issue 9 (14th January 2013) - Poddutoori, Prashanth K.; Zarrabi, Niloofar; Moiseev, Andrey G.; Gumbau‐Brisa, Roger; Vassiliev, Serguei; van der Est, Art
Abstract Two self‐assembled supramolecular donor–acceptor triads consisting of AlIII porphyrin (AlPor) with axially bound naphthalenediimide (NDI) as an acceptor and tetrathiafulvalene (TTF) as a secondary donor are reported. In the triads, the NDI and TTF units are attached to AlIII on opposite faces of the porphyrin, through covalent and coordination bonds, respectively. Fluorescence studies show that the lowest excited singlet state of the porphyrin is quenched through electron transfer to NDI and hole transfer to TTF. In dichloromethane hole transfer to TTF dominates, whereas in benzonitrile (BN) electron transfer to NDI is the main quenching pathway. In the nematic phase of the liquid crystalline solvent 4‐(n‐pentyl)‐4′‐cyanobiphenyl (5CB), a spin‐polarized transient EPR spectrum that is readily assigned to the weakly coupled radical pair TTF.+NDI.− is obtained. The initial polarization pattern indicates that the charge separation occurs through the singlet channel and that singlet–triplet mixing occurs in the primary radical pair. At later time the polarization pattern inverts as a result of depopulation of the states with singlet character by recombination to the ground state. The singlet lifetime of TTF.+NDI.− is estimated to be 200–300 ns, whereas the triplet lifetime in the approximately 350 mT magnetic field of the X‐band EPR spectrometer is about 10 μs. In contrast, in dichloromethane and BN the lifetime of the charge separation is <10 ns.